A medical corrosion-resistant coating material and its preparation method and application
By using corrosion-resistant coating materials composed of epoxy resin, aliphatic polyamines and wollastonite powder, the corrosion problem of metal medical devices in the body fluid environment is solved, good adhesion and corrosion resistance are achieved, the service life of the device is extended and the release of toxic substances is reduced.
Patent Information
- Application Number
- CN202411776665.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-05
AI Technical Summary
When metal medical devices are used in the human body for a long time, they are prone to failure due to body fluid corrosion, and some materials may release toxic metal ions, affecting human safety.
The medical corrosion-resistant coating material composed of epoxy resin, aliphatic polyamines, wollastonite powder, etc. is used to improve the corrosion resistance and adhesion of the metal substrate through the cross-linking network.
It significantly improves the corrosion resistance and service life of metal medical devices, ensures good adhesion and low toxicity of the coating material, and reduces the risk of corrosion and the release of toxic metal ions.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of medical coatings, and in particular to a medical corrosion-resistant coating material and a preparation method and application thereof. Background Art
[0002] Metal materials are widely used in the medical industry due to their good mechanical properties and biocompatibility. However, in the actual clinical application of metal medical devices such as metal implants and surgical instruments, as the medical devices are used in the human body for a long time, metal materials gradually expose problems such as inability to resist corrosion by human body fluids and easy decomposition and failure in the complex body fluid environment, resulting in a decrease in mechanical properties or even failure, greatly shortening the service life of the medical devices. In addition, some metal materials may also release toxic metal ions, causing inflammatory and immune reactions, posing potential dangers to human safety. Therefore, improving the corrosion resistance of medical devices has become a key issue that needs to be solved urgently.
[0003] In order to solve the corrosion resistance problem of metal materials, the existing technical means mainly include surface treatment and coating protection. Surface treatment technology is to improve the corrosion resistance of metal by changing the surface properties of the metal, such as electroplating, chemical plating, anodizing, etc. However, electroplating and chemical plating may introduce harmful substances, thus affecting safety and biocompatibility. The thickness of the oxide film formed by anodizing is limited, and it is difficult to completely avoid the occurrence of corrosion. Coating protection is to apply an anti-corrosion layer on the metal surface. Common coating materials include polyurethane, fluorocarbon coatings, etc. Although these coating materials have improved the corrosion resistance of metal materials to a certain extent, there is still a problem of poor adhesion in practical applications. After long-term use, the coating is prone to fall off, resulting in corrosion risks.
[0004] Therefore, it is particularly important to develop a corrosion-resistant coating material with good adhesion and biocompatibility. Summary of the invention
[0005] In order to overcome the poor adhesion of coating materials, the present application provides a medical corrosion-resistant coating material and a preparation method and application thereof.
[0006] In the first aspect, the present application provides a medical corrosion-resistant coating material, which adopts the following technical solution:
[0007] A medical corrosion-resistant coating material, comprising the following components in parts by weight: 75-120 parts of epoxy resin, 15-30 parts of aliphatic polyamine, 20-30 parts of wollastonite powder, 3-8 parts of curing accelerator, and 3-5 parts of lubricant;
[0008] The epoxy resin is tetrahydrophthalic acid diglycidyl ester and dicyclopentadiene type phenolic epoxy resin in a weight ratio of 1: (0.8-2.3).
[0009] The present application provides a medical corrosion-resistant coating material, which has good corrosion resistance and chemical resistance, and has good adhesion on the surface of the metal substrate. Specifically, the epoxy compound of the epoxy resin and the aliphatic polyamine curing agent can form a cross-linked network during the curing process, so that the coating material has excellent corrosion resistance, effectively prevents the metal substrate from being eroded by the body fluid environment, and prolongs the service life of the metal medical device; in addition, the epoxy resin curing system contains polar groups such as epoxy groups and amine bonds with relatively high activity, which can give the epoxy curing material excellent adhesion to the polar substrate of the medical device metal; the aliphatic polyamine can achieve rapid curing of the epoxy resin at a lower temperature, ensuring the corrosion resistance and low toxicity of the coating material; the addition of wollastonite powder enhances the mechanical properties and wear resistance of the coating material, and the curing accelerator and lubricant can optimize the process performance of the coating material, ensuring its stability and reliability in practical applications.
[0010] In this application, the type and ratio of epoxy resin will affect the corrosion resistance of the medical corrosion-resistant coating material and its adhesion on the surface of the metal substrate. Through experimental research, it was found that the medical corrosion-resistant coating material prepared by using diglycidyl tetrahydrophthalate and dicyclopentadiene phenolic epoxy resin with a weight ratio of 1: (0.8-2.3) as the epoxy resin has good corrosion resistance and good adhesion on the surface of the metal substrate.
[0011] In some embodiments, the weight ratio of diglycidyl tetrahydrophthalate to dicyclopentadiene phenolic epoxy resin can be 1:(0.8-1.2), 1:(0.8-1.6), 1:(0.8-2.3), 1:(0.8-2.3), 1:(1.2-1.6), 1:(1.2-2.3), 1:(1.2-2.3), 1:(1.6-2.3), 1:(1.6-2.3) or 1:(1.8-2.3).
[0012] In a specific embodiment, the weight ratio of diglycidyl tetrahydrophthalate to dicyclopentadiene novolac epoxy resin may be 1:0.8, 1:1.2, 1:1.6, 1:2.0 or 1:2.3.
[0013] Optionally, the weight ratio of diglycidyl tetrahydrophthalate to dicyclopentadiene phenolic epoxy resin is 1:(1.2-2.0).
[0014] Optionally, the aliphatic polyamine is selected from one or more of diethylenetriamine, triethylenetetramine, tetraethylenepentamine and hexamethylenediamine.
[0015] Optionally, the aliphatic polyamine is a mixture of triethylenetetramine and hexamethylenediamine.
[0016] In some embodiments, the weight ratio of triethylenetetramine to hexamethylenediamine can be 1:(0.2-0.3), 1:(0.2-0.4), 1:(0.2-0.5), 1:(0.2-0.6), 1:(0.3-0.4), 1:(0.3-0.5), 1:(0.3-0.6), 1:(0.4-0.5), 1:(0.4-0.6) or 1:(0.5-0.6).
[0017] In a specific embodiment, the weight ratio of triethylenetetramine to hexamethylenediamine can also be 1:0.2, 1:0.3, 1:0.4, 1:0.5 or 1:0.6.
[0018] Optionally, the weight ratio of triethylenetetramine to hexamethylenediamine is 1:(0.3-0.5).
[0019] Optionally, the medical corrosion-resistant coating material comprises the following components in parts by weight: 100 parts of epoxy resin, 23 parts of aliphatic polyamine, 25 parts of wollastonite powder, 3 parts of curing accelerator, and 3 parts of lubricant.
[0020] Optionally, the curing accelerator is methyldiethanolamine and the lubricant is paraffin.
[0021] In the second aspect, the present application provides a method for preparing a medical corrosion-resistant coating material, comprising the following steps: putting each raw material into a reaction device, heating to 40-45°C, and reacting for 4-5 hours; then heating to 50-55°C within 10-20 minutes, reacting for 3-4 hours; then cooling to 40-45°C within 5-10 minutes, and continuing to react for 4-5 hours; introducing nitrogen into the reactor, and adding toluene, keeping warm at 35-40°C for 1-1.5 hours, and slowly cooling to room temperature; finally adding ethanol, and distilling under reduced pressure to obtain a medical corrosion-resistant coating material.
[0022] In a third aspect, the present application provides an application of a medical corrosion-resistant coating material in biomedical materials.
[0023] Optionally, the biomedical material is a metal implant or a surgical instrument.
[0024] In summary, this application has the following beneficial effects:
[0025] 1. This application adopts epoxy resin, aliphatic polyamine, wollastonite powder, etc. to prepare medical corrosion-resistant coating materials, and uses tetrahydrophthalic acid diglycidyl ester and dicyclopentadiene phenolic epoxy resin in a weight ratio of 1: (0.8-2.3) as epoxy resin. The obtained medical corrosion-resistant coating material has good corrosion resistance and good adhesion on the surface of the metal substrate, and can not fall off after long-term use.
[0026] 2. The present application further adopts an aliphatic polyamine which is a mixture of triethylenetetramine and hexamethylenediamine as an aliphatic polyamine curing agent, which can achieve rapid curing of epoxy resin and form a cross-linked network, so that the medical corrosion-resistant coating material has good corrosion resistance and low toxicity, and has a good prospect for use in metal medical devices. DETAILED DESCRIPTION
[0027] The present application provides a medical corrosion-resistant coating material, comprising the following components in parts by weight: 75-120 parts of epoxy resin, 15-30 parts of aliphatic polyamine, 20-30 parts of wollastonite powder, 3-8 parts of curing accelerator, and 3-5 parts of lubricant; wherein the epoxy resin is tetrahydrophthalic acid diglycidyl ester and dicyclopentadiene type phenolic epoxy resin in a weight ratio of 1: (0.8-2.3); the aliphatic polyamine is selected from one or more of diethylenetriamine, triethylenetetramine, tetraethylenepentamine and hexamethylenediamine. Further, the weight ratio of tetrahydrophthalic acid diglycidyl ester and dicyclopentadiene type phenolic epoxy resin is 1: (1.2-2.0); the aliphatic polyamine is a mixture of triethylenetetramine and hexamethylenediamine. Further, the weight ratio of triethylenetetramine and hexamethylenediamine is 1: (0.3-0.5).
[0028] The present application provides a method for preparing a medical corrosion-resistant coating material, comprising the following steps:
[0029] Put all the raw materials into a reactor, heat it to 40-45°C, and react for 4-5h; then heat it to 50-55°C within 10-20min, and react for 3-4h; then cool it to 40-45°C within 5-10min, and continue to react for 4-5h; introduce nitrogen into the reactor, and add toluene, keep it at 35-40°C for 1-1.5h, and slowly cool it to room temperature; finally add ethanol, and obtain a medical corrosion-resistant coating material by vacuum distillation.
[0030] In the present application, diglycidyl tetrahydrophthalate was purchased from Wuhan Smack Biotechnology Co., Ltd.; the model of dicyclopentadiene phenolic epoxy resin is DNE260, which was purchased from Jining Tangyi Chemical Co., Ltd.; the CAS number of triethylenetetramine is 38260-01-4; the CAS number of hexamethylenediamine is 143-16-8; the CAS number of diethylenetriamine is 111-40-0; wollastonite powder was purchased from Jiangxi Kete Fine Powder Co., Ltd.; the CAS number of methyldiethanolamine is 105-59-9; paraffin was purchased from Xi'an Tianzheng Pharmaceutical Excipients Co., Ltd.; the raw materials, reagents, solvents, etc. used in this application can all be obtained commercially.
[0031] The present application is further described in detail below in conjunction with embodiments and performance testing experiments.
[0032] Examples 1-5
[0033] Examples 1-5 each provide a medical corrosion-resistant coating material.
[0034] The difference between the above embodiments is that the ratio of epoxy resin is as shown in Table 1 below.
[0035] The preparation method of the medical corrosion-resistant coating material provided in Examples 1-5 comprises the following steps:
[0036] Weigh 100g of epoxy resin, 23g of triethylenetetramine, 25g of wollastonite powder, 3g of methyldiethanolamine, and 3g of paraffin respectively; put the above raw materials into a reactor, heat to 40°C, and react for 4h; then heat to 50°C within 15min, react for 3h; then cool to 45°C within 10min, and continue to react for 4h; introduce nitrogen into the reactor, add toluene, keep warm at 40°C for 1h, and slowly cool to room temperature; finally add ethanol, and obtain a medical corrosion-resistant coating material by vacuum distillation.
[0037] Table 1 Proportions of epoxy resin in the medical corrosion-resistant coating materials provided in Examples 1-5
[0038]
[0039] Embodiment 6-13
[0040] Examples 6-13 each provide a medical corrosion-resistant coating material.
[0041] The difference between the above embodiment and embodiment 3 is: the type and ratio of aliphatic polyamines are specifically shown in Table 2 below.
[0042] Table 2 Types and ratios of aliphatic polyamines in the medical corrosion-resistant coating materials provided in Examples 6-13
[0043] Comparative Example 1
[0044] Comparative Example 1 provides a medical corrosion-resistant coating material.
[0045] The difference between the above embodiments is that the epoxy resin is diglycidyl tetrahydrophthalate. Comparative Example 2
[0046] Comparative Example 2 provides a medical corrosion-resistant coating material.
[0047] The difference between the above embodiments is that the epoxy resin is a dicyclopentadiene phenolic epoxy resin. Comparative Example 3
[0048] Comparative Example 3 provides a medical corrosion-resistant coating material.
[0049] The difference between the above embodiments is that the epoxy resin is a mixture of diglycidyl tetrahydrophthalate and dicyclopentadiene phenolic epoxy resin in a weight ratio of 1:0.5. Comparative Example 4
[0050] Comparative Example 4 provides a medical corrosion-resistant coating material.
[0051] The difference between the above embodiments is that the epoxy resin is replaced by polyurethane (TPU 2363-90A).
[0052] Application Example 1-13
[0053] Application Examples 1-13 each provide a titanium alloy implant.
[0054] The difference between the above application examples is that the medical corrosion-resistant coating materials coated on the surface of the titanium alloy implant are derived from Examples 1-13 respectively.
[0055] The preparation method of the titanium alloy implant provided in Application Example 1-13 includes the following steps: heating the medical corrosion-resistant coating material to 45°C, then coating it on the surface of the titanium alloy substrate (Ti-6Al-4V titanium alloy), cooling and curing it, and obtaining a titanium alloy implant coated with the medical corrosion-resistant coating material.
[0056] Comparative Application Examples 1-4
[0057] Comparative Application Examples 1-4 each provide a titanium alloy implant.
[0058] The difference between the above application example and application example 3 is that the medical corrosion-resistant coating material coated on the surface of the titanium alloy implant is derived from comparative examples 1-4 respectively.
[0059] Performance testing
[0060] The performance of the medical corrosion-resistant coating materials provided in Examples 1-13 and Comparative Examples 1-4 was tested, and the results are shown in Table 3 below.
[0061] (1) Adhesion: Two titanium alloy implants coated with medical corrosion-resistant coating materials were prepared in parallel according to Application Examples 1-13 and Comparative Application Examples 1-4. One was used to test the initial bonding strength between the medical corrosion-resistant coating and the titanium alloy; the other was immersed in a simulated body fluid with a pH of 7.4, taken out after 60 days, and then the bonding strength between the medical corrosion-resistant coating and the titanium alloy was tested again.
[0062] The bonding strength test was carried out using the MFT-000 multifunctional material surface performance tester; the specific operation method was as follows: using a conical diamond indenter (angle 120° and radius 200μm), continuously loading a normal force of 0.1-20N, a loading rate of 20N / min, and a scratch speed of 1mm / min. At the same time, the change curves of friction force, normal force and acoustic signal with scratch distance were continuously recorded by the sensor. Critical loads Lc1 and Lc2 were set to evaluate the failure mode of the coating. Lc1 is called the first critical load, indicating that the coating is partially scratched. As the normal load gradually increases, the diamond indenter scratches the coating to contact the substrate, cracks appear at the bottom and sides of the scratch, and peeling gradually occurs, and finally the coating completely falls off (the scratch morphology is observed by an optical microscope). At this time, the friction force will suddenly change, and an inflection point can be observed on the friction curve. The load force at this inflection point is defined as the second critical load Lc2, which is used to represent the bonding strength between the medical corrosion-resistant coating and the titanium alloy substrate.
[0063] (2) Corrosion resistance: Using simulated body fluid with a pH of 7.4 as the electrolyte, a titanium alloy implant covered with a medical corrosion-resistant coating material as the working electrode, a metal platinum sheet as the auxiliary electrode, and a saturated calomel electrode as the reference electrode, an SP15-20A electrochemical workstation was used to carry out potentiodynamic polarization testing and compared with uncoated titanium alloy implants. During the test, the equilibrium open circuit potential (Eocp) was established by 1800s, and then the potentiodynamic Tafel polarization curve was recorded at a scanning speed of 0.01V / s, and the detected Tafel curve was linearly extrapolated to obtain the corrosion potential of the sample to be tested. The more positive the corrosion potential, the lower the tendency of the titanium alloy implant to corrode in simulated human body fluids.
[0064] Table 3 Performance test results of titanium alloy implants provided by Application Examples 1-13 and Comparative Application Examples 1-4
[0065]
[0066] According to the test results in Table 3, in the titanium alloy implants of Application Examples 1-13, the initial bonding strength between the medical corrosion-resistant coating material and the titanium alloy substrate is 6.37-8.39N, the bonding strength after immersion for 30 days is 6.30-8.36N, and the corrosion potential of the titanium alloy implant is -0.08~-0.21V; while the corrosion potential of the uncoated titanium alloy implant is -0.73V. Therefore, it is shown that the medical corrosion-resistant coating material provided in this application has good corrosion resistance and good bonding strength with the titanium alloy substrate, and is particularly suitable for the surface of medical devices.
[0067] From the test results of application examples 1-5 and comparative application examples 1-4, it can be seen that in Example 1-5, diglycidyl tetrahydrophthalate and dicyclopentadiene phenolic epoxy resin in a weight ratio of 1: (0.8-2.3) are used as epoxy resins, and the initial bonding strength between the obtained medical corrosion-resistant coating material and the titanium alloy substrate is 6.37-7.45N, and the bonding strength after immersion for 30 days is 6.30-7.41N, and the corrosion potential of the titanium alloy implant obtained by coating is -0.08~-0.21V; while in Comparative Example 1, only diglycidyl tetrahydrophthalate is used as epoxy resin, and the initial bonding strength between the obtained medical corrosion-resistant coating material and the titanium alloy substrate is 4.93N, and the bonding strength after immersion for 30 days is 4.72N, and the corrosion potential of the titanium alloy implant obtained by coating is -0.35V; in Comparative Example 2, only dicyclopentadiene phenolic epoxy resin is used As epoxy resin, the initial bonding strength between the prepared medical corrosion-resistant coating material and the titanium alloy substrate is 5.16N, the bonding strength after immersion for 30 days is 4.96N, and the corrosion potential of the titanium alloy implant obtained by coating is -0.29V; Comparative Example 3 uses diglycidyl tetrahydrophthalate and dicyclopentadiene phenolic epoxy resin with a weight ratio of 1:0.5 as epoxy resin, and the initial bonding strength between the prepared medical corrosion-resistant coating material and the titanium alloy substrate is 5.80N, the bonding strength after immersion for 30 days is 5.62N, and the corrosion potential of the titanium alloy implant obtained by coating is -0.24V; Comparative Example 4 uses polyurethane to prepare the medical corrosion-resistant coating material and the titanium alloy substrate. The initial bonding strength is only 5.25N, the bonding strength after immersion for 30 days is only 5.13N, and the corrosion potential of the titanium alloy implant obtained by coating is -0.22V. Therefore, it is explained that the present application uses tetrahydrophthalic acid diglycidyl ester and dicyclopentadiene phenolic epoxy resin in a weight ratio of 1: (0.8-2.3) as epoxy resin, and the obtained medical corrosion-resistant coating material has good corrosion resistance and good adhesion on the surface of the titanium alloy substrate. Further comparison shows that the initial bonding strength between the medical corrosion-resistant coating material obtained in Example 2-4 and the titanium alloy substrate is 7.13-7.45N (≥7.00N), and the bonding strength after immersion for 30 days is 7.07-7.41N (≥7.00N), and the corrosion potential of the titanium alloy implant obtained by coating is -0.08~-0.15V (≥-0.15V), indicating that the present application further controls the weight ratio of tetrahydrophthalic acid diglycidyl ester and dicyclopentadiene phenolic epoxy resin within the range of 1: (1.2-2.0), and the obtained medical corrosion-resistant coating material has better corrosion resistance and better adhesion on the surface of the titanium alloy substrate.
[0068] The test results of Examples 3 and 6-13 show that in Examples 3 and 6, only triethylenetetramine or hexamethylenediamine is used as an aliphatic polyamine curing agent, and the initial bonding strength between the prepared medical corrosion-resistant coating material and the titanium alloy substrate is 6.71-7.45N, and the bonding strength after immersion for 30 days is 6.62-7.41N, and the corrosion potential of the titanium alloy implant obtained by coating is -0.08~-0.10V; Examples 7-11 use triethylenetetramine and hexamethylenediamine in a weight ratio of 1: (0.2-0.6) as an aliphatic polyamine curing agent, and the initial bonding strength between the prepared medical corrosion-resistant coating material and the titanium alloy substrate is 7.69-8.39N ( ≥7.5N), the bonding strength after immersion for 30 days is 7.65-8.36N (≥7.5N), and the corrosion potential of the titanium alloy implant obtained by coating is -0.08~-0.09V (>-0.10V); Example 12-13 uses diethylenetriamine and hexamethylenediamine with a weight ratio of 1:0.4 or triethylenetetramine and diethylenetriamine with a weight ratio of 1:0.4 as aliphatic polyamine curing agent, and the initial bonding strength between the prepared medical corrosion-resistant coating material and the titanium alloy substrate is 7.22-7.78N, the bonding strength after immersion for 30 days is 7.08-7.63N, and the corrosion potential of the titanium alloy implant obtained by coating is -0.09~-0.10V. Therefore, it is explained that the present application further adopts triethylenetetramine and hexamethylenediamine in a weight ratio of 1: (0.2-0.6) as aliphatic polyamine curing agents, and the bonding strength between the prepared medical corrosion-resistant coating material and the titanium alloy substrate is higher. Even when in a body fluid environment for a long time, it can adhere well to the surface of the titanium alloy substrate and is not easy to fall off.
[0069] Although the present invention has been described in detail above with general descriptions and specific embodiments, it is obvious to those skilled in the art that some modifications or improvements may be made thereto based on the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all fall within the scope of protection claimed by the present invention.
Claims
1. A medical corrosion-resistant coating material, characterized in that: The invention comprises the following components in parts by weight: 75-120 parts of epoxy resin, 15-30 parts of aliphatic polyamine, 20-30 parts of wollastonite powder, 3-8 parts of curing accelerator and 3-5 parts of lubricant; The epoxy resin is diglycidyl tetrahydrophthalate and dicyclopentadiene phenolic epoxy resin in a weight ratio of 1: (1.2-2.0).
2. The medical corrosion-resistant coating material according to claim 1, characterized in that: The aliphatic polyamine is selected from one or more of diethylenetriamine, triethylenetetramine, tetraethylenepentamine and hexamethylenediamine.
3. The medical corrosion-resistant coating material according to claim 2, characterized in that: The aliphatic polyamine is a mixture of triethylenetetramine and hexamethylenediamine.
4. The medical corrosion-resistant coating material according to claim 3, characterized in that: The weight ratio of triethylenetetramine to hexamethylenediamine is 1:(0.3-0.5).
5. The medical corrosion-resistant coating material according to claim 1, characterized in that: The medical corrosion-resistant coating material comprises the following components in parts by weight: 100 parts of epoxy resin, 23 parts of aliphatic polyamine, 25 parts of wollastonite powder, 3 parts of curing accelerator, and 3 parts of lubricant.
6. The medical corrosion-resistant coating material according to any one of claims 1 to 5, characterized in that: The curing accelerator is methyldiethanolamine, and the lubricant is paraffin.
7. The method for preparing a medical corrosion-resistant coating material according to any one of claims 1 to 6, characterized in that: The following steps are involved: Put all the raw materials into a reaction device, heat up to 40-45°C, and react for 4-5h; then heat up to 50-55°C within 10-20min, and react for 3-4h; then cool down to 40-45°C within 5-10min, and continue to react for 4-5h; introduce nitrogen into the reactor, and add toluene, keep warm at 35-40°C for 1-1.5h, and slowly cool down to room temperature; finally add ethanol, and obtain a medical corrosion-resistant coating material by vacuum distillation.
8. Use of the medical corrosion-resistant coating material according to any one of claims 1 to 6 in biomedical materials.
9. The use according to claim 8, characterized in that: The biomedical materials are metal implants and surgical instruments.
Citation Information
Patent Citations
Kiln for clay ware
CA105599A
Bolt clipper
CA111400A
Relief valve
CA143168A
Long-acting high-mechanical strength hydrophobic alicyclic epoxy pollution flashover-resistant coating
CN106752688A
Solvent-free primer for plastic runway
CN111334159A